Safety, Quality and Processing of Fruits and Vegetables - Wiktor, Artur (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nowadays, one of the main objectives of the fruit and vegetable industry is to develop innovative novel products with high quality, safety, and optimal nutritional characteristics in order to respond, with efficiency, to increasing consumer expectations. Various unconventional technologies (e.g., pulsed electric field, pulsed light, ultrasound, high pressure, and microwave drying) have emerged and enable the processing of fruits and vegetables in a way that increases their stability while preserving their thermolabile nutrients, flavour, texture, and overall quality. Some of these technologies can also be used for waste and byproduct valorisation. The application of fast noninvasive methods for process control is of great importance for the fruit and vegetable industry. The following Special Issue "Safety, Quality, and Processing of Fruits and Vegetables" consists of 11 papers which represent a high-value contribution to the existing knowledge on safety aspects, quality evaluation, and emerging processing technologies for fruits and vegetables.